Classification of areas – criteria, definitions, methods of delimitation. Study of statistical methods - Klepacki, Bogdan (Instytut Rozwoju Wsi i Rolnictwa Polskiej Akademii Nauk, 2013)
Review of the book by Joanna Rakowska, Klasyfikacja obszarów – kryteria, definicje, metody delimitacji. Studium metodyczno-statystyczne Wydawnictwo Wieś Jutra, Warszawa 2013, 153 s.